Development and structure of the discipline “Applied chemistry in medicine” (elective course) at the school of medicine - Grekova, A.; Burdina, Ia.; Gridina, I.; Shyrykalova, A.; Reda, Abbassi; Kolomiiets, P. (Journal of Education, Health and Sport, 2024)
Along with teaching the natural science and medical principles, it is the author's proposal to create a new subject for electives, “How Applied Chemistry Helps in Medication” to see education level of medical application in higher education students within the Faculty of Medicine. This elective tries to amalgamate two different topics involving both chemistry and medicine. Besides this, it places serious emphasis on the importance of public health within the context of medical practice, of the significant role chemical principles may play in the modern health care system. Students have an opportunity to investigate subjects like environmental toxicology, pharmaceutical chemistry, and chemical risk assessment in which they can perceive the chemistry’s face with the public health field. The knowledge about disease prevention strategies, health promotion and community wellness obtained as a result can enhance the skillset students need to work towards evidence-based approaches in disease prevention. The course is designed as a 3.0 credits ECTS specified by the regulatory requirements. Thematic subjects get covered and include chemical principles, toxicology, pharmaceutical chemistry, environmental toxicology, and chemical risk assessment. Sessions are designed to provide a complete picture of the domain and the methodological toolkit, while at the same time they are interactive and practical by applying theoretical concepts to real-life situations. Introduce the development of problem-solving and critical thinking as one of the learning objectives.